THE EFFECT OF KNOWLEDGE OF MANAGEMENT, KNOWLEDGE OF INFORMATION SYSTEM AND ASSERTIVENESSON TRANSFORMATIONAL LEADERSHIP - Agus Tri Widodo (IJHCM (International Journal of Human Capital Management), 2017)
The objective of this research is to study the direct effects of knowledge of management, knowledge of information system, and assertiveness on transformational leadership of department head at PT Bank Syariah Mandiri Head Office. Quantitative method was used in this research as well as Survey Method. The data were obtained by distributing questionnaire and test, and were analyzed by using descriptive and inferential analysis with path analysis approach. This sample of this research were sixty respondent from the population of one hundred and fifty department head and selected by simple random sampling.The study finding are follow: (1)there is a direct effect of knowledge of management on transformational leadership capability, (2)there is a direct effect of knowledge of information system on transformational leadership capability, (3)there is a direct effect of assertivenesson transformational leadership capability, (4) there is a direct effect of knowledge of management on assertiveness, (5) there is a direct effect of knowledgeof information system on assertiveness. As a conclusion, the transformational leadership can be enhanced by knowledge of management, knowledge of information system, and assertiveness.